POTENTIAL CONFLICTS IN THE LAND-USE PLANNING PROCESS: A CASE STUDY OF THE RURAL COMMUNE OF OLEŚNICA (POLAND) - Grochowska, Anna; Małecka, Martyna (Quaestiones Geographicae, 2020)
The purpose of this study was to identify compatibilities of land-use patterns resulting from adjacent functions within the rural commune of Oleśnica. The analysis was made based on the relevant studies of conditions and directions of spatial planning, as well as a field inventory. The results of the studies show that the applicable planning document became a potential source of spatial conflicts. On these grounds, a negative assessment was given to the functioning spatial planning system, which, according to the premises of spatial order and sustainable development, should prevent them. The existing incompatibilities are the result of issues with coordination of the local spatial policies. As a consequence, they cause an urban development chaos, lack of proper space shaping, environmental damage and lower the residents‘ quality of life.